Galaxy clusters morphology with Zernike polynomials: The first application on Planck Compton parameter maps - Capalbo V.; De Petris M.; Cui W.; Ferragamo A.; Ruppin F.; Yepes G. (EPJ Web of Conferences, 2024)
The study of the morphology of 2D projected maps of galaxy clusters is a suitable approach to infer, from real data, the dynamical state of those systems. We recently developed a new method to recover the morphological features in galaxy cluster maps which consists of an analytical modelling through the Zernike polynomials. The validation of this approach was done on a set of high-resolution mock maps of the Compton parameter y. These maps are from hydrodynamically simulated galaxy clusters in The Three Hundred project. After this step, we apply the Zernike modelling on y-maps of local (z < 0.1) galaxy clusters observed by the Planck satellite. With a single parameter collecting the main information of the Zernike modelling, we classify their morphology. A set of mock Planck-like y-maps, generated from The Three Hundred clusters, is also used to validate our indicator with a proper dynamical state classification. This approach allows us to test the efficiency of the Zernike morphological modelling in evaluating the dynamical population in the real Planck sample.